Transition from chirping to steady NBI-driven Alfvén modes caused by magnetic configuration variations in the TJ-II stellarator. (3rd June 2016) - Melnikov, A.V.; Eliseev, L.G.; Ascasíbar, E.; Cappa, A.; Castejón, F.; Hidalgo, C.; Ido, T.; Jiménez, J.A.; Kozachek, A.S.; Krupnik, L.I.; Liniers, M.; Lysenko, S.E.; et al.
Abstract: Beam-driven Alfvén eigenmodes (AEs) have been studied in the TJ-II low-magnetic-shear flexible heliac ( B 0   =  0.95 T, 〈 R 〉  =  1.5 m, 〈 a 〉  =  0.22 m), in L-mode hydrogen plasmas with hydrogen NBI and ECR heating ( P NBI   ⩽  1.0 MW, E NBI   =  32 keV, P ECRH   ⩽  0.6 MW). In low-density plasmas in the range n e ¯   =  (0.3–1.5)  ×  10 19 m −3, a large variety of AEs have been observed in the plasma core with the heavy ion beam probe diagnostic and Mirnov coils, in the frequency range 50 kHz  <   f AE   <  380 kHz. In experiments in which the vacuum rotational transform ι is varied during the shot (dynamic configuration scan), some AEs exhibit changes in their nonlinear evolution from bursting-amplitude AEs with chirping frequency to steady-frequency AEs, and back. The range of ι intervals within which the AEs studied are chirping or steady-state is determined.